RADT-32. NATIONAL TRENDS IN RADIATION DOSE FOR LOW GRADE GLIOMAS. (9th November 2020) - Wegner, Rodney; Horne, Zachary; Abel, Stephen; Xu, Linda; Yu, Alexander; Ranjan, Tulika; Karlovits, Stephen
Abstract: BACKGROUND: Adjuvant radiation is used in patients with low grade gliomas (LGG) with high risk characteristics. Randomized trials have examined dosing schemes ranging from as low as 45 Gy to higher than 60 Gy, with no difference in outcome. We used the National Cancer Database (NCDB) to see which doses were used in this patient population, and if any difference were seen in outcome. METHODS: We queried the NCDB for patients with WHO Grade 2 brain tumors treated with surgery and adjuvant radiotherapy. We divided the cohort into dose groups: 45-50 Gy, 50.4-54 Gy, and >54 Gy. Multivariable logistic regression was used to identify predictors of low and high dose radiation. Propensity matching was used to account for indication bias. RESULTS: We identified 1, 437 patients meeting the above criteria. Median age was 45 years. Forty-eight percent had astrocytoma subtype and 70% had subtotal resection. The majority of patients (69%) were treated to between 50.4-54 Gy. Half of all patients were treated with radiation alone. 1p19q status was recorded in 32% of patients, and 13% overall were co-deleted. Predictors of high dose radiation were increased income, astrocytoma subtype, chemotherapy receipt, and treatment in 2014. Patients treated to a dose of >54 Gy had a median survival of 73.5 months and was not reached in those treated to a lower dose (p=0.0041). Subset analysis of patients with astrocytoma subtype showed median survivals of 79.0 and 51.2 months for low and high dose, respectively (p=0.13). When limited to oligodendrogliomas corresponding 5 year survival rates were 86% and 65%, in favor of lower doses (p=0.0004). CONCLUSIONS: This analysis shows that 50.4-54 Gy is the most widely used radiation regimen for ow grade gliomas. There appeared to be no benefit to higher doses, although factors not recorded are likely confounding the RESULTS: